Analysis of the Impact of Online Collaborative Learning, Metacognitive Awareness, and Instructional Media Richness on Students' Problem-Solving Skills in Higher Education - Nasruliyah Hikmatul Maghfiroh (West Science Interdisciplinary Studies, 2025)
This study analyzes the impact of online collaborative learning, metacognitive awareness, and instructional media richness on students’ problem-solving skills in higher education. Using a quantitative research design, data were collected from 150 university students through a Likert-scale questionnaire and analyzed using SPSS version 25. Validity and reliability tests confirmed that all measurement items were appropriate and consistent. Classical assumption tests also indicated that the regression model met the required statistical criteria. The results of multiple linear regression analysis show that online collaborative learning, metacognitive awareness, and instructional media richness each have a positive and significant effect on problem-solving skills. Metacognitive awareness was found to be the strongest predictor, followed by online collaborative learning and media richness. The model explains 62.3% of the variance in students' problem-solving skills, indicating a strong combined influence of cognitive, social, and technological factors. These findings highlight the importance of integrating collaborative learning strategies, metacognitive training, and rich instructional media to enhance problem-solving abilities in higher education settings.